Red and blue photo-selective nets optimize leaf photostructure and photosynthetic efficiency to enhance antioxidant capacity, yield, and quality in adzuki bean - Yin, Congpei; Shi, Zhaojin; Li, Dongxiao; Tian, Cheng; Li, Yuancong; Dong, Weixin; Zhang, Yuechen (Frontiers in Plant Science, 2025)
Adzuki bean (Vigna angularis L.) is a characteristic economic crop with ecological adaptability and industrial potential. During crop production and cultivation, regulating light quality through photo-selective nets or films has become an important environmental control strategy for optimizing their yield and quality. This experiment studied the effects of different color photo-selective nets (red photo-selective net, RN; blue, BN; yellow, YN; green, GN; natural light, CK) on the yield, quality, agronomic traits, photosynthetic characteristics and antioxidant capacity of adzuki beans. The results demonstrate that, compared with CK, RN treatment significantly increased plant height (12.23%) and total dry weight (18.04%), while BN treatment significantly enhanced stem diameter (8.15%), root dry weight (21.62%) and root-shoot ratio (23.53%). RN and BN treatments both optimized the anatomical structure of leaves, showing that palisade tissue and spongy tissue increased significantly by 8.68%, 49.74% and 21.01%, 66.96% respectively compared with CK. This is possibly related to the increased net photosynthetic rate (RN: 23.18% and BN: 14.44% higher than CK) and stomatal conductance (RN: 15.82% and BN: 21.65% higher than CK) to minimize photosynthetic “noon break” depression, and ultimately enhancing the light energy conversion efficiency and actual light energy capture efficiency of the PSII reaction center. Under both RN and BN treatments, the activities of antioxidant enzymes (SOD, POD, CAT) were enhanced to suppress reactive oxygen species (ROS) accumulation; Meanwhile, the malondialdehyde (MDA) content was correspondingly reduced by 11.62% and 39.08% compared to CK. Crucially, RN treatment significantly enhanced the yield of adzuki beans (15.05%), starch content (4.69%), and total phenol content (20.00%) compared to CK. BN treatment substantially increased yield (10.63%), soluble protein content (7.69%), amino acid content (9.55%), and total flavonoid content (38.05%). Under GN treatment, although the yield of adzuki beans decreased (8.56%) and the net photosynthetic rate reduced (2.25%), the total flavonoid content of adzuki beans significantly increased by 51.21%. In conclusion, the red and blue light treatments enhance both photosynthetic capacity and yield and improve quality traits in adzuki beans, offering novel insights into optimizing light environments in cultivating specialized legume varieties.